The Use of Geotechnical Instrumentation to Optimise an Engineered Mine Design at Beaconsfield Gold Mine, Tasmania - P B. Hills; R J. Walton (The Australasian Institute of Mining and Metallurgy, 2008)
Geotechnical instrumentation has been implemented as a key step for monitoring and optimising an engineered mine design for managing seismicity at the Beaconsfield Gold Mine. Measurements of displacement, stress change, ground control element load and seismic response of the rock mass allow for back analysis and calibration of critical parameters for feedback into the engineering design loop. Instrument clusters are installed in strategic locations prior to the commencement of stoping in order to determine the nature of the response of the rock mass to stoping. A selection of instruments including instrumented cable bolts and rod extensometers, resistance wire extensometers, hollow inclusion stress cells, vibrating wire stress meters and resistance wire extensometers are used to gather data through a data logging system. The rate at which data is recorded is adjusted to provide more information during periods of anticipated rapid change such as around stope firings or during periods of high seismic activity, and less information during periods of anticipated quiescence. The twofold purpose of the instrumentation is to calibrate the numerical modelling output which forms the basis of the engineered mine design, and to provide an alert mechanism where the behaviour of the rock mass is not what was anticipated, or where the impact of that behaviour may compromise the integrity of the engineered ground control system. The paper describes the location of instrument clusters with respect to stoping, the type of instruments employed and the method of data acquisition. It provides examples of results obtained and illustrates the way in which that information is used to optimise the mine design and manage seismicity.